Study on biohydrogen production using different type of carrier materials in attached growth system - Ashah M.A.; Lutpi N.A.; Wong Y.S.; Ong S.A.; Malek M.A. (Institute of Physics Publishing, 2023)
Activated carbon; Effluents; Gas emissions; Global warming; Glucose; Granular materials; Greenhouse gases; Palm oil; Scanning electron microscopy; Attached growth systems; Bio-hydrogen production; Granular activated carbons; Hydrogen concentration; Hydrogen production rates (HPR); Modified gompertz equations; Palm oil mill effluents; Renewable energies; Hydrogen production